Mother India - Brunetti, Rafaele (Italy, 2011)
Jhuma and Niladri are a couple from Burdwan, India. They have been married for 8 years and have no children. This is a major problem in India, where a childless married woman is considered impure. In an effort to save Jhuma's reputation, the couple travels to Hyderabad, the heart of Indian medical and assisted reproduction research. Their journey of hope reveals much about the role of women and children in Indian culture.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films